Aplikasi Sistem Pakar untuk Mendiagnosa Virus Covid-19 pada Manusia Berbasis Web Menggunakan Metode Forward Chaining - Sari Noorlima Yanti; Endah Budiyati (Jurnal Informatika Universitas Pamulang, 2020)
The Covid-19 virus is currently a pandemic in the world community. This virus spreads through human-to-human contact with many media. Human lungs are organs in the human body that are vulnerable to the Covid-19 virus attack. This virus attacks through stages that are predicted to take several days. The stages from a person making contact with a sufferer of the Covid-19 virus until he is tested positive are different. Some of the factors that play a role in the attack of the spread of this virus are in addition to a person's immune weakness such as age, immunity, obesity, medical history, hygiene and the supplements a person takes. One of the ways to deal with the Covid-19 pandemic is to provide accurate information on how to prevent the spread of this virus. This information is expected to provide input to everyone in order to prevent infection. An important role in a person's life is to maintain cleanliness in daily activities to prevent contracting this virus, which has many deaths due to contracting the Covid-19 Virus. A person's knowledge and little information will be affected if they fail to maintain their health from the Covid-19 Virus attack. This situation requires an expert who is well aware of the virus and all its symptoms. This research can help us to diagnose someone's health and anticipate having a risk of contracting the Covid-19 virus by designing and implementing it. The Covid-19 Expert System was designed on a web basis using the programming languages PHP and MySQL. In this expert system, several questions are asked. After all the questions are answered, the results of the diagnosis and suggestions can appear that can help diagnose the Covid-19 Virus attack.